Dry sliding tribological characteristics of HVOF-WC/DLC duplex coating in the temperature range of RT-400 °C - Zhang, Yingpeng; Ramachandran, Chidambaram Seshadri; Wang, Qun (Materials today communications, 2025)
The high-velocity oxygen-fuel sprayed WC-20Cr3C2-7Ni (HVOF) coating was treated using a linear ion source (LIS) process to obtain HVOF-DLC (Hybrid) coating. The mechanical and tribological properties of HVOF coating before and after DLC film modification were investigated from RT-400 °C. The results showed that the hardness and toughness of Hybrid coating were significantly improved at various temperatures compared to HVOF coating. In addition, due to the overlaying of DLC film on the HVOF coating, the wear rate of the Hybrid coating was reduced by half and the coefficient of friction (COF) was also substantially low at RT-400 °C due to its high hardness and self-lubricating properties. The mechanical and tribological properties of the HVOF coating and the Hybrid coating degraded with increasing temperature. The degradation mechanisms of the two coatings were the decomposition and oxidation of carbides and the graphitization of DLC film, respectively. In short, the overlaying of the DLC thin film on the HVOF coating greatly enhanced its mechanical and tribological properties from RT-400 °C. [Display omitted] •The first report on the tribological behavior of WC-20Cr3C2-7Ni/DLC duplex coating in a wide temperature range.•The duplex coating exhibited superior mechanical properties compared to HVOF coating at RT-400 °C.•The DLC overlay significantly improved the wide temperature range tribological performance of HVOF coating.•The degradation mechanisms of the HVOF and duplex coatings were decomposition/oxidation and graphitization.